Variation in Human Research Ethics Committee and governance processes throughout Australia: a need for a uniform approach. Issue 11 (13th April 2021) - Dudi‐Venkata, Nagendra N.; Cox, Daniel R. A.; Marson, Nicholas; Tan, Lorwai; Pockney, Peter; Muralidharan, Vijayaragavan; Watson, David I.; Richards, Toby
Abstract: Background: In Australia, ethics committees across different states vary in application, requirement and process for the ethical review and approval for clinical research. This may lead to confusion and delays in the enablement of multicentre research projects. This study explores the effect of differing processes for Ethics and Governance in the establishment of the CovidSurg‐Cancer study during the global COVID‐19 pandemic. Methods: An anonymous, structured web‐based questionnaire was designed using the Research Electronic Data Capture application (REDCap) platform to capture consultant surgeons, fellows, and trainees experience in the ethics application process. 'CovidSurg‐Cancer' was an international multicentre collaborative study to assess the impact of COVID‐19 on the outcomes of patients undergoing cancer surgery. The ethics process to set up this observational study was used as to explore the differing processes applied across Australia. Results: The CovidSurg‐Cancer study was successfully set up in 14 hospitals. Four hospitals approved the study directly as an audit. Of the remaining sites, 10 ethics applications underwent Human Research Ethics Committee review following which two (14%) were subsequently approved as an audit activity and eight hospitals (57%) were given formal ethical approval with waiver of consent. Ethics application acceptance from another Australian Human Research Ethics Committee was provided with six applications; however, only three were reciprocated without the requirement for further agreements. A third of (30%) respondents suggested that the details of the application pathway, process and documentation were unclear. Conclusion: Ethics processes are varied across Australia with considerable repetition. A centralized, harmonized application process would enhance collaborative research. Abstract : Ethics processes are varied across Australia with considerable repetition. A centralized, harmonized application process would enhance collaborative research.